2016
DOI: 10.3998/ark.5550190.p009.447
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum triflate catalyzed Povarov reaction for the synthesis of pyranotetrahydroquinolines

Abstract: An efficient three component Povarov reaction is developed for the synthesis of pyrano[3,2-c]-tetrahydroquinolines using a catalytic amount of Al(OTf) 3 as a Lewis acid catalyst, in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For instance, 25 mol% of GdCl 3 triggered the three-component reaction to deliver excellent yields of the corresponding THQs 516 and 517 with good diastereoselectivity (Scheme ). In addition, Sc­(OTf) 3 , BF 3 ·OEt 2 , NbCl 5 , , Sm­(OTf) 3 , ceric ammonium nitrate (CAN), CeCl 3 ·7H 2 O/NaI, and Al­(OTf) 3 were also employed as catalysts for the same reaction. This chemistry was applied to the synthesis of hexahydro 2 H -pyrano­[3,2- c ]­quinolines as selective σ 1 receptor ligands .…”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
“…For instance, 25 mol% of GdCl 3 triggered the three-component reaction to deliver excellent yields of the corresponding THQs 516 and 517 with good diastereoselectivity (Scheme ). In addition, Sc­(OTf) 3 , BF 3 ·OEt 2 , NbCl 5 , , Sm­(OTf) 3 , ceric ammonium nitrate (CAN), CeCl 3 ·7H 2 O/NaI, and Al­(OTf) 3 were also employed as catalysts for the same reaction. This chemistry was applied to the synthesis of hexahydro 2 H -pyrano­[3,2- c ]­quinolines as selective σ 1 receptor ligands .…”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
“…N-Benzylideneaniline (2a) is widely available from suppliers and was purified by recrystallization (from hexane) before use. 1-Vinyl-2-pyrrolidinone (3), N-methyl-N-vinylacetamide (5), and 3,4-dihydro-2H-pyrone (10) are commercially available and were purified by distillation before use. (E)-1-(1-Propenyl)-2-pyrrolidinone (7) was prepared according to the procedure described in the literature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Among the numerous methods for preparing the tetrahydroquinoline ring system, the aza-Diels–Alder-type reaction between N -arylimines and functionalized alkenes is one of the most versatile approaches, because a wide range of diverse products can be readily obtained with this reaction merely by changing the combination of imines and alkenes . It is well-known that the [4+2] cycloaddition reactions between N -arylimines and functionalized alkenes are catalyzed by Brønsted acids, or by Lewis acids that include group-3 metal triflates, Sb 2 (SO 4 ) 3 , SbCl 3 , InCl 3 , FeCl 3 , Al­(OTf) 3 , and others. , Some of these reactions catalyzed by Lewis acids were extended to the asymmetric reaction by combination with chiral ligands or by using chiral organocatalysts. , It has also been reported that the cycloaddition reaction is promoted via single electron transfer by using a pyrrilium salt under UV irradiation, cerium­(IV) salt, nitrosonium salt, or an aminium cation radical . However, these methods also have some drawbacks from the viewpoint of efficient and practical catalytic reaction, namely, they require expensive rare metals with relatively large catalyst loading (1–10 mol%, in many cases).…”
mentioning
confidence: 99%
See 1 more Smart Citation